Mediasi Dalam Tiga Sistem Hukum Dan Perannya di Dalam Terwujudnya Keberhasilan Tujuan Hukum di Indonesia - Taufik Siregar; Zaini Munawir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study examines how the mediation process according to PERMA No. 1 of 2016, how the level of effectiveness of mediators in resolving cases in the Court and how the role of mediation in realizing the successful realization of legal objectives in Indonesia. The research method used is empirical juridical research, namely legal research conducted by examining directly to the field where the object under study is by direct observation of the 5 (five) State Procurement; Medan, Lubuk Pakam, Binjai, Stabat, Tanjung Balai. Preliminary data on the success of national mediation in 2017 in the MA Case Search Information System (SIPP) is only around 4.14%. The amount is a combination of mediation success in the general court and religious court. The 4.14% success data is based on real data that was successfully displayed in the mediation report menu at SIPP MA. The data source was drawn from the local SIPP of each court in Indonesia. From the description above, it can be understood that mediation is a necessity that must be applied by the judiciary in order to settle disputes peacefully, the application of the principle of justice fast, low cost and simple, and to suppress the accumulation of cases that occur. Data on mediation in successful trials nationwide is less than 4%. Mediation that was expected to be an alternative solution turned out to be devoid of achievement. As a Suggestion For judges appointed as mediators must change the mindset that, the implementation of this mediation is not just to carry out an anich rules, but further than that is that dispute resolution between parties who are parties can be carried out by peaceful means based on agreement.